Intracellular Pathways Involved in Bone Regeneration Triggered by Recombinant Silk–Silica Chimeras. (4th September 2017) - Martín‐Moldes, Zaira; Ebrahimi, Davoud; Plowright, Robyn; Dinjaski, Nina; Perry, Carole C.; Buehler, Markus J.; Kaplan, David L.
Abstract: Biomineralization at the organic–inorganic interface is critical to many biology material functions in vitro and in vivo. Recombinant silk–silica fusion peptides are organic–inorganic hybrid material systems that can be effectively used to study and control biologically mediated mineralization due to the genetic basis of sequence control. However, to date, the mechanisms by which these functionalized silk–silica proteins trigger the differentiation of human mesenchymal stem cells (hMSCs) to osteoblasts remain unknown. To address this challenge, silk–silica surfaces are analyzed for silica–hMSC receptor binding and activation, and the intracellular pathways involved in the induction of osteogenesis on these bioengineered biomaterials. The induction of gene expression of αVβ3 integrin, all three mitogen‐activated protein kinsases, as well as c‐Jun, runt‐related transcription factor 2, and osteoblast marker genes is demonstrated upon growth of the hMSCs on the silk–silica materials. This induction of key markers of osteogenesis correlates with the content of silica on the materials. Moreover, computational simulations are performed for silk/silica‐integrin binding which show activation of αVβ3 integrin in contact with silica. This integrated computational and experimental approach provides insight into interactions that regulate osteogenesis toward more efficient biomaterial designs. Abstract : This work describes the intracellular pathways leading to osteogenesis for recombinant silk‐chimera proteins with potential in regenerative medicine . Using an integrated computational‐experimental approach, insight into key interactions for control of osteogenesis is provided, demonstrating involvement of integrin αVβ3, and mitogen‐activated protein kinase pathways in osteogenic markers induction promoted by silica surfaces. This is critical for optimized designs for mineralized materials.